Liquid tissue surrogates for X‐ray and CT phantom studies. Issue 12 (31st October 2017) - FitzGerald, Paul F.; Colborn, Robert E.; Edic, Peter M.; Lambert, Jack W.; Bonitatibus, Peter J.; Yeh, Benjamin M.
Abstract : Purpose: To develop a simple method for producing liquid‐tissue‐surrogate (LTS) materials that accurately represent human soft tissues in terms of density and X‐ray attenuation coefficient. Methods and materials: We evaluated hypothetical mixtures of water, glycerol, butanol, methanol, sodium chloride, and potassium nitrate; these mixtures were intended to emulate human adipose, blood, brain, kidney, liver, muscle, pancreas, and skin. We compared the hypothetical densities, effective atomic numbers (Zeff ), and calculated discrete‐energy CT attenuation [Hounsfield Units (HU)] of the proposed materials with those of human tissue elemental composition as specified in International Commission on Radiation Units (ICRU) Report 46. We then physically produced the proposed LTS materials for adipose, liver, and pancreas tissue, and we measured the polyenergetic CT attenuation (also expressed as HU) of these materials within a 32 cm phantom using a 64‐slice clinical CT scanner at 80 kVp, 100 kVp, 120 kVp, and 140 kVp. Results: The predicted densities, Zeff, and calculated discrete‐energy CT attenuation of our proposed formulations generally agreed with those of ICRU within < 1% or < 10 HU. For example, the densities of our hypothetical materials agreed precisely with ICRU's reported values and were 0.95 g/mL for adipose tissue, 1.04 g/mL for pancreatic tissue, and 1.06 g/mL for liver tissue; the discrete‐energy CT attenuation at 60 keV of our hypothetical materials (and ICRU‐specified compositions) were −107 HU (−113 HU) for adipose #3, −89 HU (−90 HU) for adipose #2, 56 HU (55 HU) for liver tissue, and 31 HU (31 HU) for pancreatic tissue. The densities of our physically produced materials (compared to ICRU‐specified compositions) were 0.947 g/mL (0.0%) for adipose #2, 1.061 g/mL (+2.0%) for pancreatic tissue, and 1.074 g/mL (+1.3%) for liver tissue. The empirical polyenergetic CT attenuation measurements of our LTS materials (and the discrete‐energy HU of the ICRU compositions at the mean energy of each spectrum) at 80 kVp were −104 HU (−113 HU) for adipose #3, −87 HU (−90 HU) for adipose #2, 59 HU (55 HU) for liver tissue, and 33 HU (31 HU) for pancreatic tissue; at 120 kVp, these were −83 HU (−83 HU) for adipose #3, −68 HU (−63 HU) for adipose #2, 55 HU (52 HU) for liver tissue, and 35 HU (33 HU) for pancreatic tissue. Conclusion: Our method for formulating tissue surrogates allowed straightforward production of solutions with CT attenuation that closely matched the target tissues' expected CT attenuation values and trends with kVp. The LTSs' inexpensive and widely available constituent chemicals, combined with their liquid state, should enable rapid production and versatile use among different phantom and experiment types. Further study is warranted, such as the inclusion of contrast agents. These liquid tissue surrogates may potentially accelerate development and testing of advanced CT imaging techniques and technologies.